GREEN ECONOMY: EUROPEAN EXPERIENCE AND POSSIBILITIES OF ITS USE IN UKRAINE (Innovative professional education, 2024)
The modern world faces an urgent need to change its economic paradigm to a more sustainable and ecologically balanced one. In this context, the concept of a green economy is gaining more and more importance, recognizing the need to preserve natural resources and reduce emissions of harmful substances into the atmosphere. The experience of the EU countries is a valuable source for Ukraine in the implementation of green initiatives and policies aimed at reducing the impact of the economy on the environment and creating sustainable development. The analysis of this topic will help reveal the prospects of green development in Ukraine and determine the ways of its implementation.
Keywords: green economy, EU, environmentally friendly products, renewable energy, sustainable production